ENSURING FOOD SECURITY OF UKRAINE IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Viacheslav Ivanchenkov; Oleg Glushkov; Anna Podsokha (Baltic Journal of Economic Studies)
The article presents a comprehensive examination of the current state of food security in Ukraine in the context of achieving the Sustainable Development Goals (SDGs), with a particular focus on SDG 2, which aims to achieve "Zero Hunger" globally. The objective of this article is to evaluate the present situation of food security in Ukraine within the context of sustainable development in the agricultural and food industries. The research methodology entailed a comprehensive examination of pertinent literature on the subject matter, the identification of critical problematic aspects, and an evaluation of the prevailing state of food security in the country. This was achieved through the calculation and assessment of individual food security indicators, including regional food self-sufficiency indices, population consumption indices of the main food types, and global GFSI ratings. The comprehensive nature of the research lends considerable weight to the findings. An analysis of the global economic availability of food was conducted. The fluctuations in price indices for the principal categories of foodstuffs and the shifts in the global food affordability index were examined. A comprehensive analysis was conducted to evaluate Ukraine's global ranking in terms of food security and its intrinsic value. This is an evaluation of the present supply of essential food products to the population of Ukraine. The assessment is conducted on a regional basis, with a comprehensive analysis of each area. The results demonstrated a notable disparity in the capacity to ensure food security across Ukraine's regions. The article identifies the key problematic aspects of the current state of ensuring food security in Ukraine within the context of the elements of the trilemma of sustainable development: economic, social, and environmental. The paper puts forth a conceptual framework for ensuring food security through sustainable development. The core elements of the proposed mechanism are defined as strategic state initiatives for transformative transformations towards further sustainable development of the national economy, social responsibility of agri-food businesses and food consumers, eco-innovations, and socially responsible investments. The potential impact of this mechanism is considerable, offering grounds for optimism regarding the future security and sustainability of the global economy.